Photovoltage from ferroelectric domain walls in BiFeO3 - Sanvito, Stefano (My University, 2020)
We calculate the component of the photovoltage in bismuth ferrite that is generated by ferroelectric domain walls, using first-principles methods, in order to compare its magnitude to the experimentally measured photovoltage. We find that excitons at the ferroelectric domain walls form an electric dipole layer resulting in a domain-wall driven photovoltage. This is of the same order of magnitude as the experimentally measured one, but only if the carrier lifetimes and diffusion lengths are larger than previously assumed.
PUBLISHED
Keywords: Domain walls; Excitons; Ferroelectric domains; Photovoltaic effect; Ferroelectrics; Oxides; Perovskite; DFT+U; Density functional calculations; First-principles calculations